Manual de control interno administrativo como medio para promover la eficiencia operativa en la granja avícola postoina, cantón Babahoyo - García Aguillón, Mirtha Narcisa (2013)
This research work is the "DESIGN OF A MANUALS CONTROL FOR THE INTERNAL ADMINISTRATIVE FARM POULTRY POSTOINA", in the city of Babahoyo, its main objective is to raise an adequate system of internal control to safeguard its resources, check the accuracy and veracity of your management information, promote efficiency in the operations, stimulate the observation of the policies prescribed and to achieve compliance with the goals and objectives Through the current assessment of internal control with the company, they may develop manuals of roles, responsibilities and regulatory policies for compliance with the guidelines of the various departments of the poultry as well as the manual of procedures, to serve as a guide to designing a plan of action established processes within the administrative management of the poultry farm For its elaboration were applied the methods inductive, deductive, analytical; where they knew the problem of the processes in the company, the sources and techniques, such as the surveys, questionnaires, interviews and direct observation; through the constant visits to the poultry information was obtained with the help of the owner and the staff that works in each of the areas; being of great help to know the flaws that exist in the business and apply the research theme, the design of the manual of internal administrative control for the poultry farm Postoina Were found to have no defined organizational structure, duplication of functions exist for some employees, lack of internal controls presenting operational deficiencies. The poultry Postoina must consider the present manual of internal administrative control, such as the tool that will allow us to perform evaluation and checks to the processes that will be of great utility to achieve efficiency in the processes of the company.